Regulation of cell proliferation and tumor suppressor roles of microRNA 329-3p of the MAP kinase pathway in cervical squamous carcinoma - Elfansu; Rashid, Faria; Abirami, K.; Krishnamoorthy, Sivakumar; Aherkar, Kshitija; Mythreyi, R.; Murali, Uthamalingam; Basalingappa, Kanthesh M.; Jagannathan, Selvaraj; Boojhana, E.; Maghimaa, M. (Recent Research in Science and Technology, 2024)
Cervical squamous cell carcinoma is observed as the second major cause of mortality worldwide. A highly conserved mitogen-activated protein kinase (MAPK) signaling pathway occurs in a wide range of cellular processes which includes differentiation, proliferation, migration, senescence, and apoptosis. MAPK pathway can be activated by various extracellular signals, capable of generating responses as per the cell type. Thus, alteration of the EGFR receptor in this particular pathway leads to the condition of cancer due to abnormal activation of receptor tyrosine kinases. The characteristic features of microRNA (miRNA) which are endogenous, single-stranded, small non-coding RNA for their role in RNA silencing and post-transitional regulation of gene expression have been studied over the years. The miRNA functions by base pairing with the complementary sequences within the mRNA molecule. One such miRNA, miR-329-3p has a critical tumor suppressor role in the MAPK pathway, however, is least understood. Therefore, miRNA could be considered as a potential biomarker for diagnosis, prognosis, and therapeutic purposes and brought out to its fullest use to mankind.